Optimisation of conditions of phosphorus release from pharmaceutical waste sludge. Issue 1 (14th December 2018) - Zeng, Ping; Li, Juan; Cheng, Jianguang; Song, Yonghui; Wei, Jian
Abstract : With the short supply of phosphorus (P) resources all over the world, more and more phosphorus-rich excess sludge is produced. In this study, a pharmaceutical surplus activated sludge was subjected to alkali and ultrasonic treatment to promote the release of phosphorus. The optimisation of phosphorus release from pharmaceutical surplus activated sludge by alkali and ultrasonic treatment was investigated. The response surface methodology was adopted to optimise the conditions for phosphorus and organic matter release. A quadratic model was established to describe phosphorus and organic matter release. The variance was analysed by using the Design-Expert software, and the optimum operation conditions were decided on. The results indicated that the quadratic model could well fit the relationship between the release of phosphate phosphorus (PO4 3− -P) and chemical oxygen demand (COD) and the influencing factors. The order of influence on the release of phosphate phosphorus and COD was as follows: pH > total solids > ultrasonic power > time. The maximum release of phosphate phosphorus was 15·3%.